(untitled) - Woronoff, Jon (Tokyo, Japan, 1986)
Contents: Prologue: looking east; Part 1. The places; Part 2. The policies; Part 3. The prospects; Epilogue: Learning from East Asia
Keywords: Đông Á,East Asia; Điều kiện kinh tế,Economic conditions